1995
DOI: 10.1002/ajpa.1330960104
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric variation and the population history of Ireland

Abstract: Genetic variation among human populations can reflect a combination of contemporary patterns of gene flow and genetic drift as well as long-term population relationships due to population history. We examine the likely impact of past history and contemporary structure on the patterns of anthropometric variation among 31 counties in Ireland (made up of the two nations of the Republic of Ireland and Northern Ireland). Data for 17 anthropometric measures and parent-offspring migration on 7,214 adult Irish males w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 29 publications
2
46
0
Order By: Relevance
“…Had the consequences of the famine resulted in mass relocation within Ireland rather than mass emigration, then we should expect that the relationship between surname distributions and geography would have been compromised. The observed persistence of the pre-nineteenth century settlement effects is in line with the observation made by Relethford and Crawford (1995) that at both a county and a regional scale the effects of the Great Famine (on population structure inferred from anthropometrics) were minimal. The outcome is also consistent with the results of earlier smaller-scale analysis of isonymy in the Ards Peninsula, County Down (Smith et al, 1990;Smith and Bittles, 2002).…”
Section: Resultssupporting
confidence: 86%
“…Had the consequences of the famine resulted in mass relocation within Ireland rather than mass emigration, then we should expect that the relationship between surname distributions and geography would have been compromised. The observed persistence of the pre-nineteenth century settlement effects is in line with the observation made by Relethford and Crawford (1995) that at both a county and a regional scale the effects of the Great Famine (on population structure inferred from anthropometrics) were minimal. The outcome is also consistent with the results of earlier smaller-scale analysis of isonymy in the Ards Peninsula, County Down (Smith et al, 1990;Smith and Bittles, 2002).…”
Section: Resultssupporting
confidence: 86%
“…What is lacking in Boas' immigrant study, and what has not been demonstrated yet since Boas, is that environmental plasticity plays a more important role than genetic variation. What has been demonstrated is that cranial dimensions are capable of revealing ''genetic'' patterns in human populations over time and space (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). Finally, we address the issue of why Boas published such seemingly erroneous conclusions.…”
Section: Discussionmentioning
confidence: 95%
“…[35][36][37] Thus, analysis of this population may provide advantages in genetic studies of complex diseases. In terms of position and function, NOD2 is an excellent candidate gene for IBD.…”
Section: Genetics Of Ibd In Irelandmentioning
confidence: 99%